PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI PENDIDIKAN DASAR TAHAP AWAL (LOWER PRIMARY EDUCATION) NURUZZAHRO KOTA CILEGON - Setiawati, Setiawati; Ilham Maliki, Budi; Mutoharoh, Mutoharoh; Yustika Rini, Ratu; Bayi Tabrani, Mohamad (LPPM Universitas Bina Bangsa, 2025)
This study aims to describe the role of the principal in improving teacher performance at Nuruzzahro Lower Primary Education, Cilegon City. The principal holds an important responsibility in guiding, mentoring, and motivating teachers to carry out their duties optimally. This research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The research subjects consisted of the principal and teachers at Nuruzzahro Lower Primary Education. The results show that the principal actively contributes to enhancing teacher performance through regular supervision, motivation, training, and by creating a supportive work environment. The principal also establishes effective communication and maintains good relationships with all educators. These efforts have a positive impact on improving discipline, responsibility, and professional competence among teachers. Therefore, it can be concluded that the principal plays a significant role in improving teacher performance at Nuruzzahro Lower Primary Education. Effective leadership is a key factor in enhancing the quality of education.